Merger dan Kinerja Pembiayaan Konsumer PT Bank Syariah Indonesia Area Surabaya Raya - Randradivi Ariadi, Puput (Jurnal Etnik: Ekonomi-Teknik, 2023)
PT Bank Syariah Indonesia is one of the currently developing Islamic banks, PT Bank Syariah Indonesia was established on February 1, 2021. PT Bank Syariah Indonesia is the result of a merger of three Islamic banks, namely Bank Syariah Mandiri - Bank BRI Syariah and Bank BNI Syariah. The objectives to be achieved from this study based on the formulation of the problems that have been proposed are: 1) Obtain empirical evidence whether the merger strategy has differences in the performance of consumer financing before and after the merger when viewed from indicators of disbursement of financing realization. 2) Obtain empirical evidence whether the merger strategy has differences in the performance of consumer financing before and after the merger when viewed from the quality indicators of customer payments. 3) Obtain empirical evidence whether the merger strategy has differences in the performance of consumer financing before and after the merger when viewed from the productivity indicators of consumer marketing employees. The research method that will be used in the Merger and Consumer Financing Performance of PT Bank Syariah Indonesia is descriptive statistics. This study evaluates the concept theoretically and this research uses quantitative methods. The data analysis used is descriptive statistics, normality test and pair t test through the SPSS program